Needs Analysis of E-Module for Linear Motion Integrated with Problem Based Learning and Education for Sustainable Development to Facilitate Critical Thinking Skills - Reilizah Bima Aliva; Emiliannur Emiliannur; Asrizal Asrizal; Hayyu Yumna (Journal of Innovative Physics Teaching, 2026)
The rapid advancement of digital technology and the demands of twenty-first-century education require instructional materials that foster students' critical thinking skills and sustainability competencies. However, physics learning on the topic of linear motion is still dominated by conventional teaching materials that provide limited opportunities for contextual problem-solving and meaningful learning experiences. Therefore, this study aimed to identify instructional needs as a basis for developing a Canva Site-based e-module integrating Problem-Based Learning (PBL) and Education for Sustainable Development (ESD) to facilitate senior high school students' critical thinking skills. This study employed a Research and Development (R&D) method using the 4D development model, limited to the Define stage. Data were collected through critical thinking tests, student questionnaires, and teacher interviews involving 34 eleventh-grade students and one physics teacher at SMAN 9 Padang. The findings showed that students' critical thinking skills were relatively low, with an average score of 37.12%, while the interpretation indicator obtained the lowest percentage (29.4%). In addition, 86% of students expressed interest in digital learning materials. These findings indicate a need for the proposed e-module to support interactive, meaningful, and sustainability-oriented physics learning, providing a foundation for developing innovative digital learning resources that enhance students' critical thinking skills.